The Awareness of Indonesian Students Toward Autonomous Learning - Dony Marzuki (Politeknik Negeri Padang, 2013)
This writing reports the finding of a quantitative study which sought to find out the awareness of Indonesian students toward autonomous learning. This was a survey to twelve Indonesian students at their first year at Flinders University. The survey used adapted and revised questionnaire about autonomous learning which was answered on-line by respondents. Survey Gizmo was utilized for this purpose. Analysis of the data by using SPSS ver. 15.0 showed that most Indonesian students from various different background such as gender, age, hometown, occupation, and field of study have already aware of autonomous learning at almost the same level. Little different of autonomous learning level appeared on the comparison to hometowns of respondents. Respondents from Java had higher level of autonomous learning than those from outside Java. Since this study involved small proportion of Indonesian students in a specific place of Australia, similar study needs to be conducted with wider scope to find out the real condition.